Challenged Iconography: The Last Folio in the Cycle of the Life and Passion of Christ in the Bible of Ávila - Walker Vadillo, Mónica A. (’Ilu. Revista de Ciencias de las Religiones, 2007)
The Bible of Ávila holds the most complete cycle of the Life and Passion of Christ of Romanesque Spain. Each image is accompanied by an inscription written in Latin which was added sometime after the folios were completed. Nevertheless, the inscriptions do not identify correctly a number of people and scenes in the cycle. One of the questionable identifications is the last folio in the cycle. This scene was identified as the Pentecost or the Descend of the Holy Spirit, yet the iconography does not represent the typical elements that are associated with the Pentecost. This article investigates other iconographic alternatives that could explain the peculiar iconography and its position at the end of the cycle.